2021
DOI: 10.3389/fbioe.2021.713639
|View full text |Cite
|
Sign up to set email alerts
|

“Microbial Wars” in a Stirred Tank Bioreactor: Investigating the Co-Cultures of Streptomyces rimosus and Aspergillus terreus, Filamentous Microorganisms Equipped With a Rich Arsenal of Secondary Metabolites

Abstract: Microbial co-cultivation is an approach frequently used for the induction of secondary metabolic pathways and the discovery of novel molecules. The studies of this kind are typically focused on the chemical and ecological aspects of inter-species interactions rather than on the bioprocess characterization. In the present work, the co-cultivation of two textbook producers of secondary metabolites, namely Aspergillus terreus (a filamentous fungus used for the manufacturing of lovastatin, a cholesterol-lowering d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 60 publications
6
48
0
Order By: Relevance
“…The experiments presented in this paper were described in terms of microbial morphology. Furthermore, the production of secondary metabolites and bioprocess kinetics was also tested in detail by Boruta et al [ 30 ], which allows for a wider discussion of the relationship between morphology and metabolism of the cocultivated filamentous microorganisms. In the experiments from ATSR2 to ATSR6, where the cocultures were initiated by the parallel introduction of precultures to the bioreactors (preculture versus preculture, Figure 1 , Figure 2 , Figure 3 and Figure 4 ), S. rimosus gained the morphological advantage over A. terreus , however its domination was not as strong as in the ATSR9 experiment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The experiments presented in this paper were described in terms of microbial morphology. Furthermore, the production of secondary metabolites and bioprocess kinetics was also tested in detail by Boruta et al [ 30 ], which allows for a wider discussion of the relationship between morphology and metabolism of the cocultivated filamentous microorganisms. In the experiments from ATSR2 to ATSR6, where the cocultures were initiated by the parallel introduction of precultures to the bioreactors (preculture versus preculture, Figure 1 , Figure 2 , Figure 3 and Figure 4 ), S. rimosus gained the morphological advantage over A. terreus , however its domination was not as strong as in the ATSR9 experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by a significant decrease in the A. terreus pellets’ projected area in cocultures (e.g., 24 h of ATSR2 A. terreus pellets’ projected area: coculture A = 1.3 × 10 6 µm 2 , monoculture A = 1.3 × 10 7 µm 2 , p < 0.001) while the sizes of the S. rimosus pellets remained the same in the mono- and co-cultures (e. g. 168 h of ATSR2 S. rimosus pellets’ projected area: coculture 1.5 × 10 5 µm 2 , monoculture A = 1.7 × 10 5 , p > 0.05). The total ion chromatograms presented by Boruta et al [ 30 ] showed that metabolic profiles of the broth composition of the cocultures and corresponding S. rimosus monocultures in ATSR2-ATSR6 were very similar. Particular attention should be paid to two S. rimosus metabolites, oxytetracycline and rimocidin, which show antibacterial and antifungal activity, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations